A replacement name for Isodactylus Hedges, Duellman, and Heinicke, 2008 - Hedges, S. Blair; Duellman, William E.; Heinicke, Matthew P. (Zootaxa, 2008)
If it had not happened so many times in the last two and a half centuries, we would be embarrassed to admit that we created a new homonym, but such is the case.  We (Hedges, Duellman & Heinicke 2008:108) proposed the generic name Isodactylus with the type species Eleutherodactylus elassodiscus Lynch (Anura: Strabomantidae) and included in the genus 13 species: Isodactylus adercus (Lynch), I. araiodactylus (Duellman & Pramuk), I. babax (Lynch), I. brunneus (Lynch), I. dolops (Lynch & Duellman), I. elassodiscus (Lynch), I. fallaciosus (Duellman), I. latens (Lynch), I. lucida (Cannatella), I. lundbergi (Lehr), I. mantipus (Boulenger), I. nigrovittatus (Andersson), and I. peraccai (Lynch).